Prospecção de plantas daninhas com potencial para fitorremediação de solos contaminados por mercúrio - Oliveira, Evandro Alves de (2022)
The contamination of soil by heavy metals is a constant environmental concern, causing incalculable damage to human, animal, and environmental health, in addition to the high costs involved in possible recovery attempts by traditional methods. The consequences of soil contamination by mercury can directly impact the food chain, the metabolism of living beings, and cause several diseases to the human population. Among the technologies employed in the recovery of areas degraded by heavy metals, phytoremediation stands out. This is the use of plants to remove or immobilize organic and inorganic contaminants in the soil or water, and is recognized as a low-cost remediation method for decontaminating areas affected by toxic metals. Certain plant species can adapt to the conditions of these contaminated soils, tolerating high concentrations of metals in their biomass, showing essential potential for environmental restoration and remediation. Thus, the prospection and identification of species that present useful characteristics for use in phytoremediation of soils is an essential task to ensure the success of the decontamination of areas degraded by toxic metals. Among the desired characteristics, besides tolerance to the contaminant, plants with rapid growth, accessible management, easy propagation, and high biomass production are essential to the process. In this study, recurring weeds were prospected in the urban perimeter of Sinop, Mato Grosso, with wide dissemination throughout the Brazilian territory, consequently, adapted to different environmental conditions, including places where artisanal and small-scale gold mining occurs, as in the Amazon region of Mato Grosso. Subsequently, the collected seeds were cultivated under natural environmental conditions in a greenhouse, under substrate contaminated with Hg2+ ion. Different responses to treatment were observed according to each species, Tridax procumbens L. and Emilia fosbergii Nicolson (Asteraceae), species whose results showed a high potential for phytoremediation of mercury in the soil using E. fosbergii, besides the phytoremediation and bioindicator characteristics in T. procumbens, plants in which we identified considerable translocation, bioconcentration and bioaccumulation factors of Hg, with distinct levels of adaptation to certain concentrations of the contaminant. The study of these evaluated plants may contribute substantially to the phytoremediation of soils contaminated by mercury at concentrations similar to those used in this work.